Study on the Influence of the Reduced Graphene Oxide Coating on the Hydrophobicity of PU Sponge for Oil Recovery - Chi, Nguyen Ha; Huong, Dao Thi Thu; Son, Nguyen Trung; Viet, Nguyen Minh; Trung, Do Quang; Tuong, Nguyen Manh; Dang, Do Van; Phuong, Nguyen Minh (VNU Journal of Science: Natural Sciences and Technology, 2023)
In order to produce a hydrophobic material for oil removal from surface waters, in this study, the reduced graphene oxide coated PU sponges (rGO@PU) were prepared by ultrasonication of PU sponges with suspension of  rGO in ethanol. The chemical structure of the rGO coatings was investigated by X-ray diffraction and FT-IR spectroscopy methods. The surface morphology of the obtained materials was also examined by SEM. The influence of the rGO loadings and the number of coatings on the hydrophobicity of the materials was investigated. The testing on the surface hydrophobicity indicated that the water drops were remained on the surface of rGO@PU for 4.5 - 5 hours. The results indicated that the best hydrophobic sponge was obtained at the rGO loading of 3 mg/mL and after three times of coatings. The water contact angle (WCA) of the optimal rGO@PU was up to 119°. The kerosene oil absorption capacity of the rGO@PU in 5 minutes is 32.34 g/g. Besides, the oil-water separation ability of the material was also investigated by passing the kerosene-water mixture through a filter funnel containing the synthesized porous material rGO@PU. The result indicated that  the separation efficiency of the material was 85%. The recyling test was conducted by squeezing the saturated absorbed sponges and applying the desorbed sponges for the next cycle tests. After 10 times of recycling, the amounts of kerosene absorption on the rGO@PU were maintained from 4.39 - 5.33 g, implying the excellent recyclability of the material.